Distinct spermiogenic phenotypes underlie sperm elimination in the Segregation Distorter meiotic drive system. - Marion Herbette; Xiaolu Wei; Ching-Ho Chang; Amanda M Larracuente; Benjamin Loppin; Raphaëlle Dubruille (PLoS Genetics)
Segregation Distorter (SD) is a male meiotic drive system in Drosophila melanogaster. Males heterozygous for a selfish SD chromosome rarely transmit the homologous SD+ chromosome. It is well established that distortion results from an interaction between Sd, the primary distorting locus on the SD chromosome and its target, a satellite DNA called Rsp, on the SD+ chromosome. However, the molecular and cellular mechanisms leading to post-meiotic SD+ sperm elimination remain unclear. Here we show that SD/SD+ males of different genotypes but with similarly strong degrees of distortion have distinct spermiogenic phenotypes. In some genotypes, SD+ spermatids fail to fully incorporate protamines after the removal of histones, and degenerate during the individualization stage of spermiogenesis. In contrast, in other SD/SD+ genotypes, protamine incorporation appears less disturbed, yet spermatid nuclei are abnormally compacted, and mature sperm nuclei are eventually released in the seminal vesicle. Our analyses of different SD+ chromosomes suggest that the severity of the spermiogenic defects associates with the copy number of the Rsp satellite. We propose that when Rsp copy number is very high (> 2000), spermatid nuclear compaction defects reach a threshold that triggers a checkpoint controlling sperm chromatin quality to eliminate abnormal spermatids during individualization.